Design and Implementation of WebGIS Marine Ecotourism Area, Tegal Island, Lampung Province - ahmad herison; Yuda Romdania; Ahmad Zakaria; Sandy Kusuma (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2019)
Tegal Island has the potential and diversity of marine tourism which is an attraction for tourists. However, information is not yet available that can help tourists in knowing the objects and tourist areas contained in Tegal Island. This research presents tourism information in Tegal Island in the form of a Geographic Information System map. The mapping method is done using Quantum GIS software with the help of the QuickMapServices (QMS) plugin to display Google Earth imagery and the qgis2web plugin to convert QGIS files (.qgz) into web maps (WebGIS) and the presence of tourist index input. The mapping results obtained digitization of each tourist object and facility on Tegal Island in the form of shapefiles (.shp) as well as information displayed on the attribute table layer. WebGIS is used as a media for GIS map renderers that is easily accessed and adjusted according to the JavaScript Leaflet library (open source). Map of Geographic Information Systems makes it easy for people to convey and search for tourist information on Tegal Island.